Evaluation Of International Safety Management (ISM) Code Implementation Using Quantitative Descriptive Methods And Quality Function Deployment On Crossing Ship - Syuhada, David Noer; Putranta, A.A. BGS. Dinariyana Dwi (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The International Safety Management Code (ISM Code) has been coming into force for passenger ferries in Indonesia since 1998—ships that are mandatory to apply the ISM Code are subject to audit periodically by the competent authorities. Even so, there are still many non-conformities found in the implementation of the ISM Code, also the number of ship accidents is not significantly reduced to close to zero accidents. It is necessary to carry out an analysis related to the implementation of the ISM Code from another point of view, hence from the point of view of the implementing party of the ISM Code. In this research, the level of implementation analysis is measured by the requirement elements in the ISM Code and the existing obstacles. Design/methodology/approach: The method used is a mixed method, which is quantitative methods and Quality Function Deployment (QFD). Quantitative methods are carried out by means of literature studies, interviews, and surveys by distributing questionnaires. Findings: The results of the quantitative method are analyzed and followed by the QFD method with the main instrument the House of Quality (HOQ), to obtain input (technical response) from ISM Code experts. The technical response is then selected based on priority level and will become a proposal for improving the level of implementation of the ISM Code. The ship data taken in this study are passenger ferries which are serving route of Lembar - Padangbai and Lembar - Kayangan. From the results of the descriptive quantitative analysis, ten indicators of implementation and five indicators of obstacles were obtained and became priorities for improvements. Based on these results, twenty-two priority technical responses were obtained to improve the implementation of the ISM Code on passenger ferries serving routes of Lembar – Padangbai and Lembar – Ketapang. Paper type: Research paper